Global challenge of manual suapicion: Boko Haram uprising in Nigeria - Shuriye, Abdi Omar; Adeyemi, Bello K.; Huud, Shittu (Centre for Promoting Ideas (CPI), USA, 2013)
The emergence of Boko Haram uprising in 2002 in the Northern part of Nigeria has continued to pose serious threats to Nigeria’s national security. Religious sensitivity and a long time economic marginalisation of the north favor the growth of the insurgence in the region. Going by the weak approach form of the government, the recurrent violence may continue for some time. This paper provides an insight of the historical background of the group. It examines the causes and factors that enhance the group to flourish only in the Northern part of the country. The paper further outlines the origins and evolution of Boko Haram from its inception to the present. It criticises the reports of other authors as being biased and evaluates the impacts of the insurgence.